Optic nerve sheath diameter and its association with brain swelling in pediatric cerebral malaria: a retrospective study - Raees, Madiha Q.; Gushu, Montfort Benard; Taylor, Terrie E.; Seydel, Karl B.; Wynkoop, Hunter J.; O’Brien, Nicole F. (Frontiers in Pediatrics, 2024)
Introduction Mortality in pediatric cerebral malaria (CM) in low- and middle-income countries (LMICs) is associated with brain swelling on magnetic resonance imaging (MRI); however, MRI is unavailable in most LMICs. Optic nerve sheath diameter (ONSD) measurement is an inexpensive method of detecting increased intracranial pressure compared with the invasive opening pressure (OP). Our primary objective was to determine if increased ONSD correlated with brain swelling on MRI in pediatric CM. Our secondary objective was to determine if increased ONSD correlated with increased OP and/or poor neurological outcome in pediatric CM. We hypothesized that increased ONSD would correlate with brain swelling on MRI and increased OP and that ONSD would be higher in survivors with sequelae and non-survivors. Methods We performed a retrospective chart review of children aged 0–12 years in Blantyre, Malawi, from 2013 to 2022 with CM as defined by the World Health Organization. Brain swelling on admission MRI was characterized by brain volume scores (BVS); severe swelling was scored as 7–8, mild-to-moderate as 4–6, normal as 3. The admission ONSD was measured via ultrasound; it was defined as abnormal if it was >4.5 mm in children >1 year and >4 mm in children <1 year. Favorable outcome was defined as a normal neurological exam on discharge in survivors. The primary and secondary objectives were evaluated using Spearman's correlation; and the demographics were compared using chi-square and the Kruskal–Wallis test (Stata, College Station, TX, USA). Results Median age of the 207-patients cohort was 50 months [interquartile range (IQR) 35–75]; 49% (n = 102) were female. Of those, 73% (n = 152) had a favorable outcome, and 14% (n = 30) died. Twenty-nine (14%) had a normal BVS, 134 (65%) had mild-to-moderate swelling, and 44 (21%) had severe swelling. ONSD was elevated in 86% (n = 178) of patients, while 12% of patients had increased OP. There was a weakly positive correlation between BVS and ONSD (r = 0.14, p = 0.05). The median ONSD was not significantly different compared by discharge outcome (p = 0.11) or by BVS (p = 0.18). Conclusion ONSD was not a reliable tool to correlate with BVS, neurological outcome, or OP in children with CM. Future studies to identify alternative methods of early identification of CM patients at highest risk for morbidity and mortality are urgently needed.